Litter consumption does not have an effect on the phytase response of Hubbard × Ross 708 broilers reared in floor pens - K.M. Bowen; M.E. Jackson; L.E. Knarr; J.S. Moritz (Journal of Applied Poultry Research, 2023)
Summary: Phytase feeding research has traditionally been conducted by rearing broilers in raised wire cages, whereas commercially grown broilers are reared on built-up litter. Cage-based studies may not accurately represent commercial bird performance response to phytase. Birds with access to litter consume it, possibly increasing phosphorus intake and giving the impression that lower phytase concentrations are required. The authors hypothesized that the broilers reared in cages would express a greater response to phytase relative to birds reared in floor pens because they are not consuming soluble phosphorus via litter. In both housing systems, 1,500 FTU/kg or greater increased weight and live weight gain (LWG) relative to the NC diet and all lower levels (P < 0.05). The observed response curves were comparable between the 2 systems. Tibia ash percent was also restored to PC levels with the addition of 1,500 FTU/kg or greater in both systems (P < 0.0001). Bird weight and LWG decreased and feed conversion ratio increased for birds reared in pens relative to cages (P < 0.0001). Live performance did not differ between levels of phytase on d 49. The phytase response between the housing systems was similar, indicating that consumption of litter likely does not have a significant impact on broiler performance. This particular phytase source demonstrated optimal efficacy at an inclusion of 1,500 FTU/kg on d 21.